beta-Thalassemia in American Blacks: novel mutations in the "TATA" box and an acceptor splice site. - Antonarakis, S E (1984)
beta-Thalassemia genes, although often mild in their effects, are common among American Blacks. We have begun a systematic molecular analysis of beta-thalassemia mutations in this group. DNA polymorphisms in the beta-globin gene cluster were examined among 22 beta-thalassemia chromosomes. Six different haplotypes were observed. beta-globin genes of two of these were cloned, and their phenotypes were examined both in heterologous cells upon transient expression and in vivo. The gene found in the most common haplotype (9 of 22 chromosomes) contained a single base substitution (A----G) at position -29 within the highly conserved proximal promoter element (the "TATA" box). This mutant gene directed beta-globin RNA at 25% of normal levels both in heterologous cells and in vivo. It was associated with a mild beta +-thalassemia phenotype. A different gene, isolated from an apparently rare haplotype (1 of 22 chromosomes), had a single base substitution (A----G) within the acceptor splice site of the second intervening sequence. This mutation abolished normal RNA splicing so that the only RNA made from the gene in vitro was an alternatively spliced RNA, which could not encode beta-globin. The mild deficit in beta-globin production attributable to the -29 A----G mutant allele most likely accounts for the frequently mild nature of beta-thalassemia among American Blacks.